Innovative approaches to biologic development on the trail of CT-P13: biosimilars, value-added medicines, and biobetters - HoUng Kim; Rieke Alten; Fraser Cummings; Silvio Danese; Geert D’Haens; Paul Emery; Subrata Ghosh; Cyrielle Gilletta de Saint Joseph; JongHyuk Lee; James O. Lindsay; Elena Nikiphorou; Ben Parker; et al. (mAbs, 2021)
The biosimilar concept is now well established. Clinical data accumulated pre- and post-approval have supported biosimilar uptake, in turn stimulating competition in the biologics market and increasing patient access to biologics. Following technological advances, other innovative biologics, such as “biobetters” or “value-added medicines,” are now reaching the market. These innovative biologics differ from the reference product by offering additional clinical or non-clinical benefits. We discuss these innovative biologics with reference to CT-P13, initially available as an intravenous (IV) biosimilar of reference infliximab. A subcutaneous (SC) formulation, CT-P13 SC, has now been developed. Relative to CT-P13 IV, CT-P13 SC offers clinical benefits in terms of pharmacokinetics, with comparable efficacy, safety, and immunogenicity, as well as increased convenience for patients and reduced demands on healthcare system resources. As was once the case for biosimilars, nomenclature and regulatory pathways for innovative biologics require clarification to support their uptake and ultimately benefit patients.